Effect of tehina processing and storage in the physical-chemical quality - Rababah, Taha M.; Al-U'datt, Muhammad; Al-Mahasneh, Majdi; Obaidat, Mohammad; Almajwal, Ali; Odeh, Aladdin; Brewer, Susan; Yang, Wade (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: The effect of tehina processing and storage during six months at 25°C and 35°C on total phenolics, antioxidant activity, anthocyanins, and fatty acid analysis was evaluated. Tehina processing, storage period and temperature significantly (p≤0.05) decreased total phenolics, antioxidant activity and anthocyanins contents. The results showed that raw sesame seeds had the highest total phenolics (99.98 mg GAE/100 g) and lower levels were found in dehulled unroasted sesame seeds, tehina at zero time and roasted sesame seeds (62.53, 60.61 and 47.03 mg GAE/100 g, respectively). In addition, tehina during storage showed a significant decrease in total phenolics (60.61 to 42.45 mg GAE/100 g). Raw sesame seeds had the highest antioxidant activity (0.51 mg/mL), while the tehina, dehulled unroasted and roasted sesame had antioxidant activity values of 1.21, 1.35 and 1.79 mg/mL, respectively. Also, antioxidant activity of tehina at zero time was highest (1.21 mg/mL) and lowest was in tehina stored for six months (1.70 mg/mL). Sesame seeds and tehina had low levels of anthocyanins (1.26 and 0.50 mg cya-3-glu/100 g). Fatty acid analysis showed that sesame seeds (raw, dehulled unroasted and roasted) and tehina samples contain high percent of unsaturated fatty acid oleic (C18:1) and linoleic (C18:2).Keywords: sesame seeds, phenols, antioxidant activities, anthocyaninsDOI: 10.3965/j.ijabe.20160905.2091Citation: Rababah T M, Al-U’datt M, Al-Mahasneh M, Obaidat M, Almajwal A, Odeh A, et al. Effect of tehina processing and storage in the physical-chemical quality. Int J Agric & Biol Eng, 2016; 9(5): 218－226.